2008
DOI: 10.1111/j.1574-6941.2008.00481.x
|View full text |Cite
|
Sign up to set email alerts
|

Ericoid mycorrhizal fungi are common root inhabitants of non-Ericaceae plants in a south-eastern Australian sclerophyll forest

Abstract: Fungi were isolated from the roots of 17 plant species from the families Apiaceae, Cunoniaceae, Cyperaceae, Droseraceae, Fabaceae-Mimosoideae, Lomandraceae, Myrtaceae, Pittosporaceae, Proteaceae and Stylidiaceae at a sclerophyll forest site in New South Wales, Australia. Internal transcribed spacer (ITS) restriction fragment length polymorphism (RFLP) and sequence comparisons indicated that the isolated fungi had affinities to a range of ascomycetes, basidiomycetes and zygomycetes. Four RFLP types had closest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 41 publications
5
44
0
Order By: Relevance
“…kaempferi (Planch.) E.H. Wilsonhair roots while Chambers et al (2008) noted that some fungal isolates formed ErM coils in the ericaceous roots and DSE association in the roots of non-ericaceous plants. In this study, a single mycelium simultaneously developed structures corresponding to ErM and DSE association in a single ericaceous root.…”
Section: Discussionmentioning
confidence: 96%
“…kaempferi (Planch.) E.H. Wilsonhair roots while Chambers et al (2008) noted that some fungal isolates formed ErM coils in the ericaceous roots and DSE association in the roots of non-ericaceous plants. In this study, a single mycelium simultaneously developed structures corresponding to ErM and DSE association in a single ericaceous root.…”
Section: Discussionmentioning
confidence: 96%
“…We also observed a large number of ericoid-like fungi on our root samples, as well as dominance of the communities in terms of frequency and abundance by Meliniomyces, a genus that forms ericoid mycorrhizae. This may not be surprising, as an increasing number of studies have found ericoid mycorrhizal fungi colonizing the roots of tree species in the family Pinaceae and other nonericoid plant species (13,33). Whether tree roots act as alternative or primary hosts for these fungi in the absence of ericaceous plants is uncertain.…”
Section: Downloaded Frommentioning
confidence: 99%
“…were once considered specific to plant species in the Ericaceae taxon, recent findings suggest that these fungi associate with other plant taxa. However, their role in plant establishment is not well understood Chambers et al, 2008). The only ECM fungal species unique to the chestnuts was a fungus from Cantharellales (Fig 2.).…”
Section: Resultsmentioning
confidence: 99%